2022
DOI: 10.3390/cells11172734
|View full text |Cite
|
Sign up to set email alerts
|

Apigetrin Promotes TNFα-Induced Apoptosis, Necroptosis, G2/M Phase Cell Cycle Arrest, and ROS Generation through Inhibition of NF-κB Pathway in Hep3B Liver Cancer Cells

Abstract: Apigetrin (7-(β-D-glucopyranosyloxy)-4′,5-dihydroxyflavone), a glycoside bioactive dietary flavonoid derived from Taraxacum officinale and Teucrium gnaphalodes, is known to possess anticancer, antioxidant, and anti-inflammatory effects on numerous cancers. In the present study, we examined the effect of apigetrin in Hep3B hepatocellular cancer cell line (HCC). Apigetrin inhibited cell growth and proliferation of Hep3B cells, as confirmed by MTT and colony formation assay. We used apigetrin at concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Rubiarbonol-B (Ru-B), a natural arborinane triterpenoid extracted from Rubia philippinesis , switches apoptosis to necroptosis by upregulation of RIPK1 phosphorylation and NOX-1-derived ROS generation in colorectal cancer cells [ 269 ]. Bhosale et al [ 270 ] reported that administration of apigetrin, a glycoside dietary bioactive flavonoid, triggered both apoptosis and necroptosis in human Hep3B hepatocellular cancer cells via inhibition of NF-κB subunit phosphorylation (p-p65) and the IκB pathway. In addition, protein-bound polysaccharides (PBPs) have shown anti-tumor activity in MCF-7 breast cancer cells and SKMel-188 melanoma by ROS-mediated necroptosis [ 271 ].…”
Section: Therapeutic Applications Of Necroptosis Regulationmentioning
confidence: 99%
“…Rubiarbonol-B (Ru-B), a natural arborinane triterpenoid extracted from Rubia philippinesis , switches apoptosis to necroptosis by upregulation of RIPK1 phosphorylation and NOX-1-derived ROS generation in colorectal cancer cells [ 269 ]. Bhosale et al [ 270 ] reported that administration of apigetrin, a glycoside dietary bioactive flavonoid, triggered both apoptosis and necroptosis in human Hep3B hepatocellular cancer cells via inhibition of NF-κB subunit phosphorylation (p-p65) and the IκB pathway. In addition, protein-bound polysaccharides (PBPs) have shown anti-tumor activity in MCF-7 breast cancer cells and SKMel-188 melanoma by ROS-mediated necroptosis [ 271 ].…”
Section: Therapeutic Applications Of Necroptosis Regulationmentioning
confidence: 99%
“… 46 Apigenin possessed anticancer, antioxidant, and anti-inflammatory effects, including inhibiting cell growth and proliferation in Hep3B cells. 47 It was reported that diosmetin could inhibit the progression of cancer. Diosmetin also exhibited antitumor effects on HCC cells by inhibiting cell proliferation via cell cycle arrest and interfering with lipid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of these studies suggested a promising therapeutic application of these molecules in the treatment of GI cancers. [135] The overexpression of heterogeneous nuclear ribonucleoprotein A1 (HNRNP A1) has been observed to enhance the proliferation, migration, and invasion of HCC cells, promoting tumor growth, and delaying senescence. As evaluated through mechanistic tests, silence of HNRNP A1 has been found to promote the expression of P16INK4, causing cell cycle arrest.…”
Section: Necroptosis and Proliferation Invasion And Metastasis Of Gi ...mentioning
confidence: 99%
“…The findings of these studies suggested a promising therapeutic application of these molecules in the treatment of GI cancers. [ 135 ]…”
Section: Role Of Necroptosis In Gi Cancersmentioning
confidence: 99%